A hemispheric dust storm affecting the Atlantic and Mediterranean in April 1994: Analyses, modeling, ground-based measurements and satellite observations - Ozsoy, E; Kubilay, N; Nickovic, S; Moulin, C (Journal of Geophysical Research: Atmospheres, 2001)
One of the largest recorded dust tranpsort events originating from the great Sahara desert during April 1994 affected the entire region extending from the Caribbean to the Eurasian continent. This hemispherical transport of airborne dust took place during a series of storms that developed during the first three weeks of April in a background of low-index circulation. These repeated events are studied through the combined analyses and interpretation of atmospheric data, ground-based aerosol measurements, visibility observations, AVHRR and Meteosat visible band satellite data, and the results of Eta model simulations, including an aerosol transport component. The observations produce a consistent picture of the temporal and spatial development of the dust events, whose main features are used in parts to verify the model results. The rate of dust suspension from some areas of the western Sahara desert exceeded 1.5 mg m(-2) h(-1) and the maximum column integrated dust load reached 2 g m(-2) during April 3-5 1994, when the first major suspension event produced two simultaneous pulses of dust moving in opposite directions across the subtropical Atlantic Ocean and the eastern Mediterranean Sea. These dust suspensions were created by surface winds resulting from subsidence on the northeastern side of a blocking anticyclone in the Atlantic region and subsequent winds of an intense developing cyclone in the Mediterranean-African region. In the following period, maximum dust loads of 4.5 and 2.5 g m(-2) occurred on April 12 and 17, respectively, when new cyclones transported dust across the Mediterranean from Africa to Europe. The generation of the two dust pulses during the first even and the recurrent cyclone transport in the following period is shown to be the result of a large-scale, anomalous atmospheric circulation connected with blocking in the Atlantic Ocean and the interactions of tipper air jets downstream of the blocking. The particular state of the hemispheric circulation during the studied period corresponded to the positive phase of the North Atlantic Oscillation (NAO). While previous statistical evidence has consistently linked dust transport in the region with the NAO signatures, we show the same connection on the basis of this case study.